Salicylic acid as attenuator of drought stress on germination and initial development of sesame - Adriana C. da Silva; Janivan F. Suassuna; Alberto S. de Melo; Rayssa R. Costa; Wellerson L. de Andrade; Duval C. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Sesame is an important crop in Northeast Brazil, where climate conditions require adapted genotypes and alternatives for plant defense against drought. This study aimed to evaluate the salicylic acid as drought attenuator in sesame genotypes. The experiment evaluated six genotypes (BRS Seda, CNPA-G2, CNPA-G3, CNPA-G4, LAG-Branquinha and LAG-Pretinha), five osmotic potentials (0, -0.2, -0.4, -0.6 and -0.8 MPa) and three seed treatments (soaking in distilled water, in salicylic acid and no treatment). CNPA-G4 is tolerant to drought in the germination stage. Salicylic acid at 10-5 M induced tolerance to drought stress in sesame, but it is necessary to test other concentrations.